Dual‐Responsive Janus Membrane by One‐Step Laser Drilling for Underwater Bubble Selective Capture and Repelling. Issue 21 (11th September 2019) - Wu, Sizhu; Meng, Dong; Chen, Chao; Shi, Lu‐An; Zhou, Lili; Huang, Zhouchen; Li, Jiawen; Hu, Yanlei; Wu, Dong
Abstract: Achieving the dynamic control of underwater gas bubbles (UGBs) on smart surfaces has aroused great attention for academic research and industrial applications. To date, developing a kind of stimuli‐responsive porous membrane with asymmetric wettability which can be reversibly switched between Janus and non‐Janus systems, unfortunately, has been rarely demonstrated. Here, a light/temperature‐responsive Janus tapered‐hole arrayed zinc foil (TAZF) is unfolded by combining one‐step laser drilling and a subsequent heating which is successfully utilized for underwater bubble unidirectional transport, that is, bubble "diode." Moreover, this TAZF can reversibly switch between Janus architecture and double‐faced aerophobic by applying alternative heating and UV dispositions for selectively capturing or repelling bubbles. The underlying mechanism revealed by X‐ray photoelectron spectroscopy spectrums is that the reversible graft and removal of hydroxyl (OH) on the top surface of TAZF dominates the wettability conversion. The quantitative relationship among the UV and heating time and the water contact angle and the underwater bubble contact angle (UGBCA) is also studied. This work provides insight for designing smart surfaces applicable in fast bubble capture, transportation, collection, and gas/liquid separation. Abstract : A light/temperature‐responsive Janus tapered‐hole arrayed zinc foil (TAZF) is fabricated by combining one‐step laser drilling and a subsequent heating, which is successfully utilized for underwater bubble unidirectional transport, that is, bubble "diode." Moreover, the TAZF can reversibly switch between Janus architecture and double‐faced aerophobic by applying alternative heating and UV dispositions for selectively capturing or repelling bubbles.